Palace Networks at the Court of Carlos II: Maria Anna of Palatinate-Neuburg’s Confessor, Gabriel Pontifeser, and the Queen’s German Chamber (1690–1700) - Kozák, Valentina Marguerite (Renaissance and Reformation / Renaissance et Réforme, 2020)
The arrival in Madrid in 1690 of the future queen consort, Maria Anna of Palatinate-Neuburg (1667–1740), second wife of the Spanish king Carlos II (1661–1700), also brought about the establishment of an unofficial palace faction known as the German Chamber. Since the members of this faction were part of Maria Anna’s household, the analysis of their social activities gives insight into court practices during the last decade of Carlos II’s reign. This article intends to shed light on the new networks and agency of members of the German Chamber at the Madrid court, in particular, that of the queen’s confessor, Gabriel Pontifeser di Chiusa. By investigating the activities and new court practices within the queen consort’s household that enabled Pontifeser to build secure networks and achieve importance, the article reveals the significant power wielded by foreign courtiers at the Madrid court between 1690 and 1700.